Tractography‐Based Ventral Intermediate Nucleus Targeting: Novel Methodology and Intraoperative Validation - Francesco Sammartino; Vibhor Krishna; Nicolas Kon Kam King; Andrés M. Lozano; Michael L. Schwartz; Yuexi Huang; Mojgan Hodaie (2016)
ABSTRACT Background The ventral intermediate nucleus of the thalamus is not readily visible on structural magnetic resonance imaging. Therefore, a method for its visualization for stereotactic targeting is desirable. Objective The objective of this study was to define a tractography‐based methodology for the stereotactic targeting of the ventral intermediate nucleus. Methods The lateral and posterior borders of the ventral intermediate nucleus were defined by tracking the pyramidal tract and medial lemniscus, respectively. A thalamic seed was then created 3 mm medial and anterior to these borders, and its structural connections were analyzed. The application of this method was assessed in an imaging cohort of 14 tremor patients and 15 healthy controls, in which we compared the tractography‐based targeting to conventional targeting. In a separate surgical cohort (3 tremor and 3 tremor‐dominant Parkinson's disease patients), we analyzed the accuracy of this method by correlating it with intraoperative neurophysiology. Results Tractography of the thalamic seed revealed the tracts corresponding to cerebellar input and motor cortical output fibers. The tractography‐based target was more lateral (12.5 [1.2] mm vs 11.5 mm for conventional targeting) and anterior (8.5 [1.1] mm vs 6.7 [0.3] mm, anterior to the posterior commissure). In the surgical cohort, the Euclidian distance between the ventral intermediate nucleus identified by tractography and the surgical target was 1.6 [1.1] mm. The locations of the sensory thalamus, lemniscus, and pyramidal tracts were concordant within <1 mm between tractography and neurophysiology. Interpretation The tractography‐based methodology for identification of the ventral intermediate nucleus is accurate and useful. This method may be used to improve stereotactic targeting in functional neurosurgery procedures. © 2016 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society